Parenting Patterns in Growing the Talent of Children from Early - Wildan Islamadin, Ari; Awalin, Bobi Nurul; Fadilah, Dida Sitti; Rumaesa, Dinda; Fitri, Fitri; Maulinda, Hilma Putri; Vebrianti, Livia; Pramudya, Muhammad Adit; Aprilian, Muhammad Rivan; Fauziah, Nurlisyifa; Sholihah, Selvi Shofiatus; Athifah, Siti Nur; Wulansari, Wulansari; Apriansyah, Yossy; Sholihat, Neni (AbdimasMu UMTAS, 2025)
The Real Work Lecture (KKN-11) at the University of Muhammadiyah Tasikmalaya was held in Sukajaya Village, Cimerak District, Pangandaran Regency. Which is where the area requires guidance on parenting strategies. Then the influence of education, environment, experience and parents have a big impact on the formation of personality and character values for children. Strategies in educating are also called parenting styles, parenting styles contribute to the child's further development. A child's talent interest should be applied from an early age. Parenting styles also play an important role in the growth and development of children. Parenting style involves various interactions between children and parents that can determine how the child's moral development is further. Lack of parental knowledge regarding the use of age-appropriate applications can be a negative race for children in the future. Includeing the people of Karangjaya Hamlet, Sukajaya Village, Cimerak District, Pangandaran Regency. This problem certainly needs the attention of all parties. Because if left unchecked, it is possible that the children in Karangjaya hamlet, Sukajaya Village, Cimerak District, Pangandaran Regency will always be left behind and lack of parenting style in developing children's talents from an early age.